La biomúsica como estrategia didáctica para desarrollar el aprendizaje cognitivo en el área de comunicación en los estudiantes del 6to grado de primaria en la I.E N°00654 Lucila Portocarrero Robalino de Vela - Vásquez Lozano, Ana María (2013)
The purpose of this investigate was to conducta biomusic strategy to develop cognitiva learning in the area of communication in the sixth grade student's of primary educational in the lE No. 00654 "LucilaPortocarrero Robalino of Vela " , district of Rioja, 2013. To meet the objectives, was based on the studies of the history of research on theories : philosophical Plato - Aristotle , psychology of music Dowlingy , multiple intelligences , the formation of musical thought Moog and Contributions Piaget applied to the teaching of music in which the study variables were conceptualized, Such theoretical framework allowed the following hypothesis: lf we apply the biomusic as a teaching strategy, then develop significant cognitiva learning in the area of communication in the sixth grade student's of primary educational in the lE No. 00654 "Lucila Portocarrero Robalino of Vela" Rioja district. The research design was pretest and posttest with two experimental and control groups, which belongs to the quasi-experimental design. The sample consisted of 57 student's of the sixth grade of primary educational, with development of eight learning sessions with the implementation of the biomusic, structured play techniques, breathing, movement, active relaxation, emitting musical sounds, transfer files, active relaxation and musical evaluation. When contrastad the hypothesis, a t- calculated = 28.94 was obtained higher than T- tabulated = 1,673, with a= 0.05, determinad that biomusic as a teaching strategy developed significantly cognitiva learning in the area of communication student's in sixth grade of primary educational in the lE No. 00654 "Lucila Portocarrero Robalino of Vela" Rioja district.